Optimizing electro-thermo Helds for soot oxidation using microwave heating and metal - Al-Wakeel, H.B. (Institute of Physics Publishing, 2015)
Soot is produced by incomplete combustion of various carbon-containing compounds. Soot is one of the main environmental pollutants and has become an important environmental and specific objective. To reduce soot from exhaust emission of diesel engine, a new technique is proposed and implemented by using metal inserted in the soot exposed to electromagnetic radiation. This paper presents a simulation to obtain optimum metal length and shape that give optimum electric field for attaining temperature enough for soot oxidation using microwave heating and a thin metal rod. Four cases were numerically examined to investigate the electric field and temperature distributions in a mono-mode TE10 microwave cavity having closed surfaces of perfect electric conductors. The operating frequency is 2.45 GHz, and power supply is 1500 W. The simulation methodology is coupling the absorbed electromagnetic energy with heat transfer energy. The absorbed electromagnetic energy is found from the electric field within the soot. The simulation was run using ANSYS based on finite element method. The results of the four simulation cases show that the optimum simulation is represented by case 2 where the value of electric field is 39000 V/m and heating time to arrive at the oxidation temperature (873 K) is 35 s using cylindrical metal rod of 8 mm length. It is revealed that the concept of achieving high temperature for soot oxidation by using thin metal rod inside a microwave cavity can be applied. Â© Published under licence by IOP Publishing Ltd.